Functional outcomes of distal radial fractures by 5 pin technique - Harafan, Abdulla; Rajan Sujatha, Adarsh; Nath, Amrith K.; Krishna, Anju; Sathyan, Dhuthi Lakshmi; S., Ranjith Kumar (International Journal of Research in Orthopaedics, 2025)
Background: Distal radius fractures (DRF) are among the most common orthopaedic injuries. This study assesses the efficacy of a percutaneous five-pin fixation method for DRF, a procedure chosen for its minimal invasiveness and mechanical stability which promotes early postoperative wrist movement. We report on the clinical and functional results achieved with this technique in our patient cohort. Methods: We prospectively followed 35 patients. At the 6-month postoperative mark, wrist function was quantified using the QuickDASH questionnaire, while radiographic alignment was assessed based on the criteria defined by Sarmiento's modification of Lindstrom. Results: The mean age of patients was 45.2 years (range: 23-70 years), with a male predominance (71.4%). Road traffic accidents were the most common mode of injury (57.1%). The mean QuickDASH score at 6 months was 11.4, with 74.3% of patients achieving an excellent or good outcome. Radiological assessment showed excellent or good results in 80% of patients based on Sarmiento's criteria. Conclusions: For displaced DRF with minimal fragmentation, the five-pin method offers a valuable treatment strategy that is not only successful but also economical and tissue-sparing. It provides stable fixation, enables early mobilization, and results in functional outcomes comparable to more invasive procedures like volar plating.